SYSTEMATIZATION OF URBANIZATION PROCESSES IN THE EXAMPLE OF KASHKADARYA REGION: STATISTICS AND ANALYSIS - Rakhimova Madina Shukhrat qizi; Khidirova Shakhzoda Shukhrat qizi (Modern American Journals, 2025)
This article analyzes the state of urbanization processes in the Kashkadarya region based on demographic, economic, and infrastructural indicators of recent years. The purpose is to determine the main directions for systematizing urbanization and to develop practical recommendations for regional policy.
Keywords: Urbanization, Kashkadarya, demographic indicators, urbanization level, infrastructure, sustainable development.